The Relationship Between Metro Transport and the SDG Goals of the 2030 Agenda: A Bibliographic Review - Rocha, Thaís Reis S.; Salvador, Renan Picolo; Nascimento, Ana Paula Branco do (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT Objective – This study investigates the relationship between civil maintenance in the metro system and the Sustainable Development Goals (SDGs) of the 2030 Agenda, analyzing its contribution to sustainable urban mobility and the reduction of environmental impacts. Methodology – This is a systematic bibliographic review that identifies and analyzes existing literature on the subject. Academic publications and technical regulations, including NBR 9452, were examined, along with data on metro infrastructure and sustainability. Originality/relevance – The research fills a gap by correlating metro system maintenance with the SDGs, emphasizing the importance of transportation infrastructure for sustainable cities. The study highlights the need for technological innovation and integrated public policies to strengthen the resilience and efficiency of public transportation. Results – The findings indicate that SDG 11 (Sustainable Cities and Communities) is the most correlated with the topic, followed by SDG 3 (Health and Well-being) and SDG 12 (Responsible Consumption and Production). The analysis underscores the relevance of metro infrastructure for accessibility, safety, and quality of life in cities, while also highlighting challenges in integrating sustainable maintenance practices into urban planning. Theoretical/methodological contributions – The study reinforces the importance of regulatory standards and best maintenance practices for the conservation of large metro structures, ensuring operational safety and promoting sector sustainability. Social and environmental contributions – The research highlights the impact of metro transportation on urban mobility, equitable access to services, and the mitigation of urbanization’s environmental effects, reinforcing the need for investments in sustainable infrastructure.